Oral absorption and drug interaction kinetics of moxifloxacin in an animal model of weightlessness - Dong Liang; Jing Ma; Bo Wei (Scientific Reports, 2021)
Abstract To investigate the effect of simulated weightlessness on the pharmacokinetics of orally administered moxifloxacin and the antacid Maalox or the antidiarrheal Pepto-Bismol using a tail-suspended (TS) rat model of microgravity. Fasted control and TS, jugular-vein-cannulated, male Sprague-Dawley rats received either a single 5 mg/kg intravenous dose or a single 10 mg/kg oral dose of moxifloxacin alone or with a 0.625 mL/kg oral dose of Maalox or a 1.43 mL/kg oral dose of Pepto-Bismol. Plasma concentrations of moxifloxacin were measured by HPLC. Pharmacokinetic data were analyzed using WinNonlin. Simulated weightlessness had no effect on moxifloxacin disposition after intravenous administration but significantly decreased the extent of moxifloxacin oral absorption. The coadministration of moxifloxacin with Maalox to either control or TS rats caused significant reductions in the rate and extent of moxifloxacin absorption. In contrast, the coadministration of moxifloxacin with Pepto-Bismol to TS rats had no significant effect on either the rate or the extent of moxifloxacin absorption. These interactions showed dose staggering when oral administrations of Pepto-Bismol and moxifloxacin were separated by 60 min in control rats but not in TS rats. Dose staggering was more apparent after the coadministration of Maalox and moxifloxacin in TS rats.